Studies Of Genetic Epidemiology About Phenotype With Complex Determination In The Context Of A Biomedical Basic Sciences Doctoral Program - Herrera Martinez, Manuela; Fernández-Caraballo, Douglas; Heredia-Ruiz, Danay; de la Torre-Santos, Maria Elena; Taboada-Lugo, Noel; Salazar-Torres, Lay; González-Herrera, Lorna (Revista Cubana de Investigaciones Biomédicas, 2019)
Objective: To identify a core set of research procedures for genetic epidemiology that need to be learnt to obtain a scientific degree in subjects related to basic biomedical sciences. Methods: We discuss the results of six research projects in the area of genetic epidemiology about complex phenotypes. We show in the studied phenotypes the higher prevalence in relatives compared to the general population, the higher risk among first-degree relatives of affected individuals, and the segregation mode of each phenotype. Meanwhile, to show the influence of environmental factors and various analysis of gene-environment interaction using different models. Finally, we discuss the common research procedures followed during these studies. Results: research studies in the subject of genetic epidemiology can be divided into three broad categories: (1) those that aim at describing the distribution of a disease or a determinant at the level of a population of interest (familiar hereditary angioedema, reproductive failure); (2) those that attempt to investigate a potential aetiological link between one or more specific determinants and a disease of interest (congenital birth defects, cervix cancer, and longevity) and (3) those aimed at evaluating the effectiveness of an intervention applied to groups of individuals in the population (hypoplasia foetal thymus). Conclusions: We have identified, a set of theoretical topics as well as study techniques and methodologies for the approach of research projects in genetic epidemiology, could be considered as the general and specific bases for postgraduate teaching in relation to obtaining a doctorate in basic biomedical sciences in our University and could be useful to other Universities of similar contexts.